Parallel DNA Molecular Analysis Platform Based on a Plano-Concave Fabry–Pérot Microcavity Laser Array - Jun, Chan Seok; Lee, Wonsuk (MDPI AG, 2025)
We present a parallel DNA molecular analysis platform based on an array of plano-concave Fabry–Pérot (PC-FP) microcavity lasers that enables the simultaneous, sequence-specific detection of multiple DNA targets. Each PC-FP cavity is functionalized with a distinct probe DNA and integrated within a microfluidic channel, allowing localized hybridization and lasing emission upon optical pumping. When Cy3-labeled complementary targets were introduced, distinct lasing peaks emerged from corresponding cavities at ~607 nm, whereas single-base-mismatched sequences produced no measurable signal. The lasing threshold was approximately 0.6 µJ/mm2, confirming highly efficient optical feedback and cavity-enhanced signal amplification. The parallel operation of three PC-FP cavities demonstrated independent, multiplexed detection without optical crosstalk. The plano-concave geometry provides mode stability, compact alignment tolerance, and a tenfold reduction in threshold compared to flat FP mirrors. These results highlight the potential of PC-FP microcavity laser arrays as a scalable alternative to fluorescence-based assays, offering rapid, high-throughput DNA hybridization and melting analysis within a miniaturized solid-state architecture.